Bioactive fragments of laminin and collagen chains: lesson from the testis. Issue 3 (March 2020) - Li, Huitao; Liu, Shiwen; Wu, Siwen; Li, Linxi; Ge, Renshan; Cheng, C Yan
Abstract : Recent studies have shown that the testis is producing several biologically active peptides, namely the F5- and the NC1-peptides from laminin-γ3 and collagen α3 (IV) chain, respectively, that promotes blood–testis barrier (BTB) remodeling and also elongated spermatid release at spermiation. Also the LG3/4/5 peptide from laminin-α2 chain promotes BTB integrity which is likely being used for the assembly of a 'new' BTB behind preleptotene spermatocytes under transport at the immunological barrier. These findings thus provide a new opportunity for investigators to better understand the biology of spermatogenesis. Herein, we briefly summarize the recent findings and provide a critical update. We also present a hypothetical model which could serve as the framework for studies in the years to come.